Impact of an Educational Intervention Aimed at Nursing Staff on Oral Hygiene Care on the Incidence of Ventilator-Associated Pneumonia in Adults Ventilated in Intensive Care Unit - Melissa Sánchez Peña (Universidad de Antioquia, 2021)
Objective. This work sought to evaluate the impact of an educational intervention on oral hygiene care aimed at nursing care staff, on the incidence of Ventilator-Associated Pneumonia (VAP) in adults from an ICU in Colombia.